Jovian auroral radio source occultation modelling and application to the JUICE science mission planning. (December 2021) - Cecconi, Baptiste; Louis, Corentin K.; Muñoz Crego, Claudio; Vallat, Claire
Abstract: Occultations of the Jovian low frequency radio emissions by the Galilean moons have been observed by the PWS (Plasma Wave Science) instrument of the Galileo spacecraft. We show that the ExPRES (Exoplanetary and Planetary Radio Emission Simulator) code accurately models the temporal occurrence of the occultations in the whole spectral range observed by Galileo/PWS. This validates of the ExPRES code. In addition to supporting the analysis of the science observations, the method can be applied for preparing the JUICE moon flyby science operation planning. Highlights: The ExPRES code accurately models the occultation of Jovian radio emissions by Galilean moons. This study provides an independent validation of the ExPRES code. The method is applied for preparing the JUICE science operation planning during Galilean moon flybys.